Bioinformatics – a student's companion. (2017) - Ibrahim, Kalibulla Syed; Gurusubramanian, Guruswami; Yadav, Ravi Prakash; Kumar, Nachimuthu Senthil; Pandian, Shunmugiah Karutha; Borah, Probodh; Mohan, Surender; Zothansanga
No abstract available